Pengaruh Ukuran Perusahaan, Profitabilitas dan Likuiditas Terhadap Nilai Perusahaan Pada Perusahaan Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2025 - Hanifa Fidina; Apriya Santi; Siti Mardah (PT. Karya Inovatif Nusantara, 2026)
This study aims to analyze the effect of company size, profitability, and liquidity on firm value in food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2025. This study uses a quantitative approach with secondary data in the form of annual financial reports. The population consists of 83 food and beverage companies listed on the IDX. Using purposive sampling, 40 companies were selected with a total of 143 observations after removing outliers. The independent variables were measured using Ln (Total Assets) for firm size, Return on Assets (ROA) for profitability, and Current Ratio (CR) for liquidity, while the dependent variable was measured using Price to Book Value (PBV). Data analysis was conducted using multiple linear regression with SPSS version 27. The results indicate that: (1) Company size has a negative and insignificant effect on company value (2) Profitability has a positive and significant effect on firm value (3) Liquidity has a negative and significant effect on firm value and (4) Simultaneously, company size, profitability, and liquidity have a significant effect.